Gawai Dayak Festival and the Increase of Foreign Tourist Visits - Elyta Elyta (Global Strategis, 2021)
AbstrakGawai Dayak adalah festival tahunan di Kalimantan Barat, Indonesia dan Sarawak, Malaysia, yang memperlihatkan kekayaan seni budaya dan tradisi Suku Dayak yang berkembang baik di Kalimantan Barat maupun di Sarawak. Artikel ini mengkaji upaya yang dilakukan pemerintah Propinsi Kalimantan Barat di dalam memanfaatkan festival Gawai Dayak sebagai sarana untuk meningkatkan kunjungan wisatawan mancanegara. Bagaimana langkah-langkah yang dapat dilakukan sehingga festival Gawai Dayak mampu menjadi sarana meningkatkan jumlah kunjungn wisatawan asing ke Kalimantan Barat? Menggunakan metode deskriptif dengan pendekatan kualitatif, data yang dinalisis dalam artikel ini dikumpulkan melalui wawancara dan studi dokumentasi yang terkait dengan penyelenggaraan Gawai Dayak. Sejumlah upaya yang dilakukan pemerintah dalam membenahi tatakelola wisata di Kalimantan Barat teridentifikasi dan berpotensi menjadi instrumen soft power memperkenalkan budaya dan sekaligus menjadi sarana daya tarik wisata bagi Propinsi Kalimantan Barat. Kata Kunci: Gawai Dayak, pariwisata, soft power Gawai Dayak is an annual festival in West Kalimantan, Indonesia and Sarawak, Malaysia, which shows the richness of the arts and culture and traditions of the Dayak tribe that have developed both in West Kalimantan and in Sarawak. This article examines the efforts made by the West Kalimantan provincial government to utilize the Gawai Dayak festival as a means to increase foreign tourist visits. What steps can be taken so that the Gawai Dayak festival can be a means of increasing the number of foreign tourist visits to West Kalimantan? Using a descriptive method with a qualitative approach, the data analyzed in this article were collected through interviews and documentary studies related to organizing the Dayak Gawai event. A number of efforts made by the government in improving tourism management in West Kalimantan have been identified and have the potential to become a soft power instrument to introduce culture and at the same time become a means of tourist attraction for West Kalimantan Province. Keywords: Gawai Dayak, tourism, soft power